2011
DOI: 10.1007/82_2011_172
|View full text |Cite
|
Sign up to set email alerts
|

Shiga Toxin Pathogenesis: Kidney Complications and Renal Failure

Abstract: The kidneys are the major organs affected in diarrhea-associated hemolytic uremic syndrome (D+HUS). The pathophysiology of renal disease in D+HUS is largely the result of the interaction between bacterial virulence factors such as Shiga toxin and lipopolysaccharide and host cells in the kidney and in the blood circulation. This chapter describes in detail the current knowledge of how these bacterial toxins may lead to kidney disease and renal failure. The toxin receptors expressed by specific blood and residen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
47
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(51 citation statements)
references
References 241 publications
0
47
0
1
Order By: Relevance
“…With regard to the intracellular response, apoptosis in microvascular endothelial cells from human renal glomeruli caused by Stx has been documented [48] and induction of apoptosis by SubAB has also been reported for a variety of cell types, including Vero and HeLa cells [30,36]. To analyze these mechanisms, we studied necrosis and apoptosis of HGEC exposed to Stx2 and SubAB.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With regard to the intracellular response, apoptosis in microvascular endothelial cells from human renal glomeruli caused by Stx has been documented [48] and induction of apoptosis by SubAB has also been reported for a variety of cell types, including Vero and HeLa cells [30,36]. To analyze these mechanisms, we studied necrosis and apoptosis of HGEC exposed to Stx2 and SubAB.…”
Section: Discussionmentioning
confidence: 99%
“…Also relevant may be the potential role of erythrocytes in the development of the microvascular lesion of HUS. It is assumed that the presence of fragmented erythrocytes during HUS is consequence of mechanical fragmentation of these cells while passing through partially occluded capillaries [48]. One study also reported that erythrocyte membranes were affected by oxidative damage during HUS [50], leading to eryptosis [51].…”
Section: Discussionmentioning
confidence: 99%
“…Infections by Stx-producing organisms can result in the onset of a disease termed the hemolytic-uremic syndrome (HUS) that is characterized by renal failure, hemolytic anemia, and thrombocytopenia. Shiga toxins are considered the key STEC virulence factor required for the onset of HUS with Stx2 being the toxin most often associated with severe disease (2)(3)(4). In the United States, HUS is the most common cause of acute renal failure in children under 5 years of age (5)(6)(7).…”
mentioning
confidence: 99%
“…While renal failure is a key feature of HUS and renal samples from patients with HUS show extensive damage (2), the temporal pattern of Stx-mediated renal damage has not been determined, and it remains unclear which renal cells are the primary targets during disease. This is largely due to an inability to monitor renal damage on a molecular and cellular level during the course of disease in human patients and to access patients during the early stages of disease progression.…”
mentioning
confidence: 99%
“…After oral ingestion and intestinal infection, STEC elaborate Stx1 and/or Stx2, and these toxins then induce systemic proinflammatory and prothrombotic pathways [4]. Approximately 15% of cases are thought to progress from STEC gastroenteritis to HUS.…”
mentioning
confidence: 99%